Effects of estrogen on functional and neurological recovery after spinal cord injury: An experimental study with rats - Letaif, Olavo Biraghi (2015)
OBJECTIVES:To evaluate the functional and histological effects of estrogen as a neuroprotective agent after a standard experimentally induced spinal cord lesion.METHODS:In this experimental study, 20 male Wistar rats were divided into two groups: one group with rats undergoing spinal cord injury (SCI) at T10 and receiving estrogen therapy with 17-beta estradiol (4mg/kg) immediately following the injury and after the placement of skin sutures and a control group with rats only subjected to SCI. A moderate standard experimentally induced SCI was produced using a computerized device that dropped a weight on the rat's spine from a height of 12.5 mm. Functional recovery was verified with the Basso, Beattie and Bresnahan scale on the 2nd, 7th, 14th, 21st, 28th, 35th and 42nd days after injury and by quantifying the motor-evoked potential on the 42nd day after injury. Histopathological evaluation of the SCI area was performed after euthanasia on the 42nd day.RESULTS:The experimental group showed a significantly greater functional improvement from the 28th to the 42nd day of observation compared to the control group. The experimental group showed statistically significant improvements in the motor-evoked potential compared with the control group. The results of pathological histomorphometry evaluations showed a better neurological recovery in the experimental group, with respect to the proportion and diameter of the quantified nerve fibers.CONCLUSIONS:Estrogen administration provided benefits in neurological and functional motor recovery in rats with SCI beginning at the 28th day after injury.